The Legal Position of Masbuk for Jum'at Prayers to the Perspective of the Syafi'i and Hanafi - Sulfanwandi Sulfanwandi (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
Masbuk is one thing that often happens in congregational prayers. In syara' terms, masbuk is a condition in which a person is left behind in part or all of the cycles of prayer in congregation following the imam. In the implementation of the Friday prayer, the laggards of the second raka'ah with the priest have legal implications that are different from the laggards of the congregation in the second raka'ah in other obligatory prayers. The most contrasting variation in the opinion of the imam of the madzhab in this regard is between the Hanafi and Shafi'i schools which also represent jumhur. The research question in this thesis is what is the opinion of the Hanafi and Syafi'i schools regarding the law of intoxication in Friday prayers, and what are the arguments and legal istinbath used by the Hanafi and Syafi'i schools regarding the law of intoxication in Friday prayers. This research found two things; first, according to the Hanafi School, the law of intoxication during the Friday prayer is obligatory for the masbuk to continue this prayer as the Friday prayer as following the prayer of the priest with two cycles of prayer. Meanwhile, according to the Syafi'i school of thought and the majority of scholars, it is obligatory for a drunken person to perform the midday prayer because he does not get the Friday prayer. Second, the argument used by each school was narrated by Abu Hurairah, but with a different hadith editorial and path. The legal istinbath method used by the Hanafi School is in the form of bayani and ta'lili reasoning. As for the Shafi'i School, it only uses bayani reasoning. From the arguments of the two, this study views that the view of the Shafi'i School has a more appropriate and well-founded argumentation, because missing the bowing in the second cycle of Friday prayers in congregation shows that a person is not only left behind in his cycles, but also left behind in his Friday prayer with the Imam.